Enhancing Water Management in Jordan: A Fresh Tomato Water Footprint Analysis - Hamaideh, Arwa; Al-Zghoul, Tharaa; Dababseh, Nuha; Jamrah, Ahmad (Jordan Journal of Agricultural Sciences, 2024)
Water footprint (WF) analysis is crucial for comprehending agricultural water usage patterns. This study aims to determine the total WF for tomatoes in Jordan from 1994 to 2023, covering both summer and winter seasons, to inform decision-making regarding tomato cultivation practices in the area. Despite inconsistencies in data recording, particularly regarding fertilizer application and sunshine, the WF serves as a valuable tool for estimating seasonal variations in water requirements and facilitating comparisons between different approaches to water usage for tomatoes. Comparative studies globally suggest variability in WFs due to factors such as climate, irrigation methods, and soil conditions influencing results. In this study, the CROPWAT 8.0 model was employed to analyze input data obtained from the Department of Statistics, NASA POWER, and local farmers near the Baqoura, Deir Alla, and Ghour Alsafi stations. The analysis aimed to determine the green WF (rainfall), blue WF (irrigation), and gray WF (water required to dilute pollutants) at these stations. The results revealed that the total WF during winter was approximately 7217.62, 8417.65, and 14061.42 m3/ton for the Baqoura, Deir Alla, and Ghour Alsafi stations. In summer, the respective values were around 3107.67, 6026.52, and 11847.35 m3/ton. Significant findings include ET green, evapotranspiration (ET) blue, crop water use (CWU) green and blue, and production yield for 2023. The nitrogen application per dunum was also calculated as 368 kg/30 dunum, equating to 123 kg/ha. The significance of these results lies in their potential to inform and optimize water management practices in tomato cultivation, promoting sustainability and resource efficiency.